Multiplicative derivative and its basic properties on time scales - Goktas, Sertac; Yilmaz, Emrah; Cigdem, Ayse (Wiley, 2022)
We define the multiplicative derivative and its properties on time scales. Then, we restate many concepts for multiplicative analysis such as derivative, Rolle's theorem, mean value theorem, and increasing-decreasing property on time scales. We aim to create important fields of study by carrying this most important issue of multiplicative analysis, which has applications in economics, finance and many other fields, to time scale calculus.
Keywords: time scale; multiplicative calculus